Labour Market Resilience and New Employment Models in the Context of Digital and Green Transformations for Sustainable Economic Development - Salimli, Ali (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
This paper provides a comprehensive analysis of the impact of digital and green transformations on the structure, functional mechanisms, and employment models of the labor market within the context of sustainable economic development. The application of digital technologies, particularly artificial intelligence, automation, and the platform economy has led to the expansion of flexible and non-traditional forms of work, such as remote work, freelancing, and platform-based employment, while fundamentally transforming the demand for skills in the labor market. At the same time, the green transformation promotes the creation of new “green jobs” in sectors such as renewable energy, energy efficiency, environmentally friendly production, and sustainable logistics, thereby contributing to the establishment of a balance between economic growth and environmental responsibility. The article assesses the opportunities and risks these processes pose for labor market resilience, substantiates the importance of human capital development, lifelong learning, and reskilling mechanisms, and emphasizes the necessity of adapting state policies, institutional reforms, and social protection systems to new employment models.